THE RELATIONSHIP AMONG LEARNING INTEREST, DISCIPLINE, AND LEARNING ENVIRONMENT WITH MATHEMATICS LEARNING OUTCOMES OF EIGHTH GRADE STUDENTS OF SMP MUHAMMADIYAH BANGUNTAPAN BANTUL REGENCY OF ODD SEMESTER IN THE ACADEMIC YEAR OF 2015/2016 - Bustanika Luthfi Harisna; Widayati Widayati (Universitas Ahmad Dahlan, 2017)
The failures of students learning are related to many factors, such as, low interest in learning something, low discipline, and less-supportive learning environment. This research intends to know the presence or absence the positive and significant correlation among learning interest, discipline and learning environment with mathematics learning outcomes of eighth-grade students of SMP Muhammadiyah Banguntapan, Bantul Regency, the first semester of the 2015/2016 academic year. The population in this research is the eighth-grade students amounting to 5 classes. The class sample was taken from the class VIII-A, and the class test was taken from the class VIII-E by random sampling technique. Data collecting technique was done by questionnaire method and testing method. The test of research instruments involves validity test, reliability test, and different power test. The test of analysis preconditions involves normality test, linearity test, and independence test. The analysis of data used product moment correlation analysis and double linear regression analysis. The result of research showed that there is a positive and significant correlation among learning interest, discipline, and learning environment with mathematics learning outcomes, as well as Å¶ = -28,5840 + 0,2766 X1 + 0,2412 X2 + 0,2788 X3 Â and SR X1= 38,181%, SR X2 = 6,593% and SR X3= 35,226%.